Correlation of carbon dioxide and systolic velocity of the middle cerebral artery in patients with spontaneous subarachnoid hemorrhage of aneurysmal origin - Juan Esteban Muñoz Montoya (Elsevier, 2022)
Background: Aneurysmal Subarachnid Hemorhage (aSAH) secondary to an aneurysm is the most common presentation of nontraumatic SAH. Worldwide, the incidence varies, affecting more frequently women with an average age of 55 years. One of its main complications is cerebral vasospasm. Objective: The objective of this study was to evaluate the correlation between blood flow of the middle cerebral artery and arterial CO2 levels in patients with aSAH, comparing those who presented vasospasm in relation to those who did not. Material and methods: Observational, historical cohort study, including patients between 18 and 85 years old, diagnosed with Aneurysmal Subarachnoid Hemorrhage (aSAH) secondary to an aneurysm (aSAH) Spearman/Pearson correlation coefficient was used to determine the correlation between mean velocity flow (MVF) by transcranial doppler and levels CO2 serum according to the analysis group (with or without vasospasm). A value <0.05 was determined for statistical significance. Results: Between 2015 and 2019 a total of 54 patients diagnosed with aSAH were treated in our institution, our results indicate a positive correlation between the SVRMCA and SVLMCA with the presence of vasospasm (p value = <0.001). No correlation was observed between serum CO2 levels and SVRMCA or SVLMCA, irrespective of the presence of vasospasm. Conclusion: In patients with aneurysmal subarachnoid hemorrhage, serum CO2 levels do not correlate with cerebral systolic velocities. Further studies are required to confirm this finding.